{Modification of Guanine with PhotolabileN-Hydroxypyridine-2(1H)-thione: Monomer Synthesis, Oligonucleotide Elaboration, and Photochemical Studies} - Vrantza, Despoina; Kaloudis, Panagiotis; Leondiadis, Leondios; Gimisis, Thanasis; Georgios C. Vougioukalakis; Orfanopoulos, Michael; Gasparutto, Didier; Cadet, Jean; Encinas, Susana; Paris, Cecilia; Miranda, Miguel A. (Helv. Chim. Acta, 2006)
The photochemistry of N-hydroxypyridine-2(1H)-thione (NHPT), inserted as a photolabile modifier at the 6-position of 2′-deoxyguanosine or guanosine, has been evaluated. In particular, 6-[(1-oxidopyridin-2-yl)sulfanyl]- (1a) and 6-[(pyridin-2-yl)sulfanyl]-2′,6-dideoxyguanosine (2a), novel photolabile derivatives of the natural nucleosides, were synthesized and characterized. The observed photolysis products of 1a in organic solvents could only be rationalized by assuming a rapid equilibrium with the corresponding 6-[(2-thioxopyridin-1(2H)-yl)oxy] analogue 3a (Scheme 5). Transient spectroscopy of 1a indicated a strong triplet-excited state suitable for triplet → triplet energy transfer or singlet-oxygen generation. The NHPT function was stable enough for (slightly modified) automated solid-phase oligonucleotide synthesis. The utility of the above compounds is discussed, as well as their potential use in photosensitization of reactive oxygen species in DNA. © 2006 Verlag Helvetica Chimica Acta AG.